An iPSC-Derived Myeloid Lineage Model of Herpes Virus Latency and Reactivation - Poole, Emma; Huang, Christopher J. Z.; Forbester, Jessica; Shnayder, Miri; Nachshon, Aharon; Kweider, Baraa; Basaj, Anna; Smith, Daniel; Jackson, Sarah Elizabeth; Liu, Bin; Shih, Joy; Kiskin, Fedir N.; et al. (Frontiers in Microbiology, 2019)
Herpesviruses undergo life-long latent infection which can be life-threatening in the immunocompromised. To date, models of latency and reactivation of human cytomegalovirus (HCMV) have depended on the use of primary myeloid cells, cells known to be important for HCMV latent carriage and reactivation in vivo. However, primary cells are limited in availability, difficult to culture and to genetically modify; all of which have hampered our ability to fully understand virus/host interactions of this persistent human pathogen. We have now used iPSCs to develop a model cell system to study HCMV latency and reactivation in different cell types after their differentiation down the myeloid lineage. Our results show that iPSCs can effectively mimic HCMV latency/reactivation in primary myeloid cells, allowing molecular interrogations of the viral latent/lytic switch. This model may also be suitable for analysis of other viruses, such as HIV and Zika, which also infect cells of the myeloid lineage.